Konseling Individual Pendekatan Sfbt Teknik Scaling Questions Untuk Mengatasi Prestasi Akademik Siswa Yang Menurun Drastis - Prakoso, Muhammad Rizky Nur; Rifai, Muhammad Aziz; Santoso, Taufik Sani (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
The decline in students’ academic achievement is not solely influenced by cognitive factors but is also closely related to psychological conditions and unfavorable family dynamics. Family conflicts, economic instability, and emotional pressure may trigger anxiety that negatively affects students’ learning concentration and academic motivation. This study aims to describe the role of individual counseling using the Solution-Focused Brief Counseling (SFBC) approach through the scaling question technique in assisting students who experience a significant decline in academic achievement. This research employed a qualitative approach with a case study design involving one high school student who experienced a noticeable decrease in academic performance over the last two semesters. Data were collected through in-depth interviews, observations during the counseling sessions, and documentation of the student's academic records. The counseling process consisted of four sessions conducted over a one-month period. The findings indicate that the implementation of the SFBC approach helped the student identify internal resources and develop more adaptive strategies for change. The scaling question technique also assisted in monitoring the student’s emotional development, as indicated by the reduction of anxiety levels from scale 8 to 4 and the improvement of learning focus and academic motivation. These findings suggest that the SFBC approach can serve as an effective and practical counseling intervention to help students overcome declining academic achievement influenced by psychosocial factors within the school context. Solution Focused Brief Therapy, Scaling Question Technique, Individual Counseling, Academic Performance Decline, School Counseling